2022
DOI: 10.1111/cns.14051
|View full text |Cite
|
Sign up to set email alerts
|

Total tau in cerebrospinal fluid detects treatment responders among spinal muscular atrophy types 1–3 patients treated with nusinersen

Abstract: AimsConsidering the substantial variability in treatment response across patients with spinal muscular atrophy (SMA), reliable markers for monitoring response to therapy and predicting treatment responders need to be identified. The study aimed to determine if measured concentrations of disease biomarkers (total tau protein, neurofilament light chain, and S100B protein) correlate with the duration of nusinersen treatment and with scores obtained using functional scales for the assessment of motor abilities.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
0
9
0
2
Order By: Relevance
“…This could contribute significantly to the disparities among the studies. Moreover, a recent study has convincingly shown that t-tau levels decrease significantly in patients with SMA 1 (but not SMA 2 and 3) when treated with nusinersen [82]. More research is needed to discover which biomarker (or combination of biomarkers) is best for predicting disease severity, evaluating therapeutic response and separating treatment responders from nonresponders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This could contribute significantly to the disparities among the studies. Moreover, a recent study has convincingly shown that t-tau levels decrease significantly in patients with SMA 1 (but not SMA 2 and 3) when treated with nusinersen [82]. More research is needed to discover which biomarker (or combination of biomarkers) is best for predicting disease severity, evaluating therapeutic response and separating treatment responders from nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 demonstrates that NfL and pNfH were used as potential pharmacodynamic (response) biomarkers in the majority of studies that examined the utility of molecular biomarkers for monitoring therapeutic response in SMA. In the majority of studies, a decrease in NfL and pNfH levels was observed following treatment with nusinersen [39,[61][62][63][76][77][78][79][80][81], whereas others observed no change in the levels of these biomarkers [45,56,60,[82][83][84] (Table 2).…”
Section: Monitoring Of Therapeutic Response In Sma Using Molecular Bi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Other recent candidate biomarkers include genetic factors such as SMN2 copy number [ 10 , 13 15 , 81 , 82 ], SMN2 polymorphisms [ 10 , 13 16 , 81 – 83 ], and modifier genes [ 73 , 84 89 ]; transcription and splicing regulators, such as microRNAs [ 90 94 ], methylation factors [ 95 99 ], and long non-coding RNAs [ 100 103 ]; biomolecular factors such as SMN protein [ 18 , 39 , 48 , 57 , 81 , 104 106 ], neurofilament (NF) [ 78 , 107 118 ], tau protein [ 112 , 119 121 ], and muscle damage indicators [ 122 124 ]; muscle imaging parameters including magnetic resonance imaging (MRI) [ 122 124 ] and electrical impedance myography (EIM) [ 75 , 125 127 ]; and electrophysiological parameters including compound muscle action potential (CMAP) [ 128 133 ], motor unit number estimation (MUNE) [ 75 , 125 127 ], and repetitive nerve stimulation [ 45 , 75 , 134 138 ].…”
Section: Introductionmentioning
confidence: 99%